HUBUNGAN JUMLAH HAFALAN SANTRI DENGAN KECERDASAN INTELEKTUAL DI PONDOK PESANTREN TAHFIDZ AL-QUR’AN MATHLA’UL ANWAR (TAQURMA) PANDEGLANG - Nurafifah, Siti; Mutaqin, Mumu Zainal; Suhayati, Eha (Institut Agama Islam Sahid (INAIS) Bogor, 2024)
Intellectual intelligence can influence the memorization process more easily, conversely memorizing the Al-Qur'an in small or large amounts can make someone smarter, both intellectually, emotionally, or spiritually. The standardization of the Mathla'ul Anwar Tahfidz Al-Qur'an Islamic Boarding School includes the amount of memorization expected from students at each class level. Each student can achieve the target set by the Islamic Boarding School, which is 6 juz. Although in general all students have the same activity schedule and methods used by the mentor, however, from the results of the recapitulation of the student achievement report in the middle of the first semester of 2024, there are striking differences in memorization achievements among students. Some students may have achieved the target of memorizing juz 2 and 3 well, while others face significant difficulties in achieving these targets. Factors that influence this difference can include various aspects, such as individual learning methods, motivation levels, support received, and other personal factors.